Keanekaragaman parasitoid dan predator Bactrocera (Diptera: Tephritidae) Di Kabupaten Demak - Dyah Rini Indriyanti; Rifki Faisal (JURNAL ILMIAH AGRINECA, 2014)
The study aims to identify the parasitoids and predators of Bactrocera spp. in Demak Regency. Five species Fruits were examined,  they were water aple (Syzygium aqueum), starfruit (Averhoa bilimbi L), guava (Psidium guajava), melinjo (Gnetum gnemon) and mango (Mangifera indica). Fruits attacked by Bactrocera were taken from five locations orchards. Bactrocera larvae  were obtained from infected fruits. They were reared in the laboratory until they become imago. Imago were  counted and identified whether it become   Bactrocera imago or parasitoids imago. To identify the predators, larvae and pupae of Bactrocera deliberately used as bait. The research found two species of parasitoids that attack Bactrocera spp. i.e Fopius arisanus and Diachasmimorpha longicaudata.  The highest parasitation (29.21%) occurred in B. mcgregogi that attacked Gnetum gnemon fruit and the lowest (3.57%) in B. carambolae that attacked  guava.  Five species Bactrocera  predators  were  found  that prey on the larvae and pupae. They were Oecophyla smaragdina, Odontoponera sp., Stagmomantis carolina, Anoplolepis gracilipes and Euborelia sp.